Democratic dilemmas : why democracies ban political parties - Bourne, Angela K. (Routledge studies in extremism and democracy, 2018)
Theory and research design : from "militant democracy" to security discourse, institutions, and democratic competition -- Ban regimes and banned parties in Spain, the United Kingdom, and Germany -- Herri Batasuna and its successors : from "Terrorist Threat" to Carrier of a "Copernican Shift" from violence -- Sinn Féin and Republican clubs : from terrorist pariah to Republicanism's pathway out of violence -- The Socialist Reich Party and National Democratic Party of Germany : from "militant democracy" to declining anti-system party threats -- Electoral systems as an alternative to party bans -- Party bans and government formation